Professional, Research, and Publishing Trends in Operations and Supply Chain Management. Issue 3 (July 2015) - Simpson, Dayna; Meredith, Jack; Boyer, Kenneth; Dilts, David; Ellram, Lisa M.; Leong, G. Keong
<x xml:space="preserve">Abstract</x> We report on the thoughts of a large group of scholars in the field of operations and supply chain management (O/SCM) regarding current and future issues facing our profession. Broad issues raised and addressed include a perceived lack of relevance in our research, calls from business school deans for faculty to increasingly fund their own research, greater demand for use of large data sets and methodological rigor, along with higher expectations for publishing. We invited four scholars who discussed these issues during an Academy of Management conference session in 2014, to present their perspectives within this essay. We then distributed the perspectives of each of these authors to O/SCM scholars globally so that they could add support, counterpoints, and extensions. Collectively, they raise important points regarding a need for greater innovation and creativity in O/SCM research, the challenges and opportunities of increased complexity and "big data, " the value of working in other research domains and collaborating with others, the promise of new technology, and the importance of improving how we communicate our value to business school colleagues. Finally, our contributors provide recommendations on how we may address these issues and continue to adapt and move our profession forward.